Legal Protection Against Unilateral Cancellation for Tenants of Shophouses Built on Cultivated Land Based on DSN-MUI Fatwa No. 112/DSN-MUI/XI/2017 - Husni, Zahra Chairawani; Tarigan, Tetty Marlina (LEGAL BRIEF, 2025)
The issue of legal protection for shophouse tenants who experience unilateral cancellation due to unclear land status, particularly when the shophouse is built on cultivated land, remains a significant challenge in Indonesia's business sector. This study employs a normative legal method by analyzing laws and regulations, fatwas, and relevant literature, with a focus on the application of DSN-MUI Fatwa No. 112/DSN-MUI/XI/2017 concerning the ijarah contract. The findings indicate that tenants are highly vulnerable to financial losses and business disruptions when shophouse owners unilaterally terminate leases, especially when land ownership status is uncertain. The fatwa provides a sharia-based explanation emphasizing the importance of ownership clarity, mutual agreement, and fair compensation in lease contracts. The implementation of DSN-MUI Fatwa no. 112/DSN-MUI/XI/2017 is considered a potential solution to address unilateral cancellations, offering legal certainty and protection for all parties, as well as serving as a basis for recommendations to policymakers and business actors in creating fair and sharia-compliant lease agreements.